Determination of Energy Capacity and Suitable Location Selection Criteria in Flexible Rock Barriers Against Rockfall Risks - Eroltan Durmuş; Özkan Coruk; Ahmet Karakaş (Doğal Afetler ve Çevre Dergisi)
Rockfall is defined as the movement of rock blocks bounded by discontinuity planes or weak zones formed according to the weathering condition of the environment on the slope surfaces or on the slope surfaces cut by technical works along the slope or slope direction under the influence of gravity. Developments in today's technology contribute to the emergence of important projects and productions in the prevention of rock falls. As a result of the measures taken, safer residential areas, safer highway and railway crossings can be established. In this study, the energy and height determinations of high energy damping flexible rock barriers, which have been manufactured as a protection measure in areas with rockfall risk in recent years, and the appropriate line criteria to be selected for the barrier were evaluated according to the results of manual calculations. During the determination of these criteria, calculated energy, speed, bounce height values and trajectories were compared with the computer software results. As a result of the comparisons, it was seen that there were no significant differences in the block bounce heights and surface contact points, but the kinetic energy values obtained in the calculations (2515 kJ) were higher than the kinetic energy result given by the computer software (1600 kJ). The difference is due to the surface friction and restitution coefficients in the surface contacts of the rock block in the computer software. In the study, surface friction and restitution coefficients were neglected in order to remain in the safe area against simultaneous or short-timed multiple block falls from the source area.